P720 Efficacy of exclusive enteral nutrition for induction and partial enteral nutrition for maintenance of remission in newly diagnosed paediatric and adolescent Crohn's disease. (25th January 2019) - Ikeda, A; Ogashiwa, T; Nakamori, Y; Mitsui, T; Chida, K; Hashimoto, Y; Tamura, Y; Maeda, S; Kimura, H; Kunisaki, R
Abstract: Background: Exclusive enteral nutrition (EEN) is beneficial for inducing remission in children, and is recommended as the first-line therapy for inducing remission for newly diagnosed paediatric patients with CD. However, the long-term effectiveness of enteral nutrition (EN) therapy, including partial enteral nutrition (PEN), has not been systematically investigated. This study aimed to investigate the efficacy of EEN for inducing remission and PEN for maintaining remission in a retrospective, observational study. Methods: We retrospectively reviewed the outcome of consecutive paediatric patients who were younger than 18 years and were newly diagnosed with active CD at our centre. The patients received EEN and PEN for inducing and maintaining remission from January 2000 to September 2018. The remission rate at Week 8 was evaluated according to the paediatric Crohn's disease activity index (PCDAI). The cumulative rate of maintaining remission was calculated using the Kaplan–Meier method. For evaluation of safety, any adverse event occurring after administration of enteral nutrition was considered. Results: Fifty-one patients were enrolled. A total of 31 (61%) patients were boys and the median age at diagnosis was 14.0 years (range: 7.0–17.0 years). Seventeen of 51 (33%) patients received EEN therapy to induce remission. Fourteen (82%) of 17 patients achieved a clinical response and nine (53%) achieved clinical remission at Week 8. Twenty-four (47%) patients received PEN therapy to maintain remission after any induction therapy, including EEN, drug therapies, and intestinal resection. Among 24 patients who received PEN after a median follow-up of 4.2 years, the cumulative rates of maintaining remission were 58% at 1 year and 36% at 3 years. Induction therapy had no effect on the timing of relapse (log-rank test, p = 0.1946). No severe adverse events occurred. Conclusions: EEN is effective for inducing remission. PEN may be effective for maintaining remission in newly diagnosed paediatric patients with CD, regardless of the type of the induction therapy. To the best of our knowledge, this is the first study to report the efficacy of EN therapy as maintenance remission therapy in newly diagnosed paediatric patients with CD, regardless of induction remission therapies.